Optimalisasi Pengelolaan Lahan Suboptimal Melalui Aplikasi Teknologi Pertanian dalam Mendukung Ketersediaan dan Ketahanan Pangan - Wahid Wahid; Edi Tando; Widya Sari Murni (Seminar Nasional Lahan Suboptimal, 2020)
Wahid W, Tando E,  Murni WS. 2020. Suboptimal land use optimization efforts through the support of agriculture technology in support national food availability and security. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The challenges in the agricultural production system in the future are very complex. The toughest challenge faced is the provision of national food. An alternative is through suboptimal land use. This paper presents information on the optimization of suboptimal land use as a solution in supporting food supply and supporting food security.  The results showed that suboptimal land has the potential to be developed as agricultural land. Suboptimal land has not been managed optimally as agricultural farming. Suboptimal land development for agriculture is facing problems with high soil acidity, Fe and Al poisoning and deficiency of macro and micro nutrients. Land management and application of agricultural technology have a strategic role in increasing suboptimal land productivity. Application of technology for selecting specific location commodities, organic fertilizers, aerobic planting, soil improvement and optimum fertilization, cropping arrangement, soil and water conservation and water harvesting play a role in suboptimal land use Implementation of agricultural technology in sustainable suboptimal land management can support national food availability and security.